Pengaruh Inventory Turn Over Dan Fixed Asset Turn Over terhadap Return on Equity pada Perusahaan Farmasi yang Terdaftar di BEI Tahun 2007-2013 - Jufrizen, Jufrizen (Jurnal Kajian Manajemen Bisnis, 2015)
This study aims to determine how the influence Inventory Turnover and Fixed Asset Turnover on Return On Equity (ROE) either partially or simultaneously in various industrial companies listed on the Indonesia Stock Exchange 2010-2013. This research approach is qualitative approach, which is based on the approach of testing and analyzing the theory composed of variables, measurement used numbers, and analyzed using statistical procedures. The population in this study is a pharmaceutical company which is listed on the Indonesia Stock Exchange in 2009-2013. The sample in this research is determined by purposive sampling. Of the 10 companies, has been acquired 8 companies that meet the criteria for the research sample. Data used in this research is secondary data. Data analysis techniques in this study adala using multiple linear regression analysis, testing classical assumptions and hypothesis testing using SPSS version 16 o'clock. These results indicate that partially Inventory Turnover significant effect on ROE with significant value 0.001 <0.05, Fixed Asset Turnover not significant effect on ROE with significance 0.625 > 0.05. Inventory Turnover variables simultaneously and Fixed Asset Turnover significant effect on Return On Equity (ROE) with significant value 0.003 <0.05